Chronology of Morphological Forms of Mycobacterium bovis Rapid-Growing Strain - Tkatschenko, A. A.; Tkatschenko, O. A.; Tkatschenko, Оleksii; Tkachenko, Olexiy; Tkachenko, A. A.; Ткаченко, Олексій Андрійович; Bilan, Maryna; Bilan, M. V.; Білан, Марина Володимирівна; Glebenyuk, Volodymyr; Glebenyuk, V. V.; Glebenyuk, V.; et al. (AVES Publishing Co., 2020)
The study aimed to examine the changes observed in the morphology of rapid-growing tuberculosis pathogen strain, degree of pathogenicity, sensitized properties, and content of lipids, which depend on the pH of the medium, for 180 inoculations of 1–3 days culture. The reversion of non–acid-resistant forms of Mycobacterium bovis of the rapid-growing strain to bacterial acid-resistant forms occurred because of the following reasons: formation of non–acid-resistant grains in thread-like M. bovis, transformation and fragmentation of non–acid-resistant thread-like forms into acid-resistant rod-shaped bacteria, and output from non–acid-resistant thread-like M. bovis acid-resistant forms. It was found that increasing the number of passages of M. bovis of the rapid-growing strain through the medium at pH 6.7 led to a probable decrease (p<0.05) in the content of total lipids; fractions of phospholipids, triacylglycerols, and sterin ethers; and an increase in the number of diacylglycerols, sterins, and free fatty acids (FFAs). It is established that the decrease in saturated and long-chain fatty acids and the increase in unsaturated and short-chain fatty acids were accompanied by the loss of virulence of mycobacteria. Of the 19 FFAs, nine tended to disappear from the cell wall. Метою дослідження було вивчення змін у морфології швидко зростаючого штаму збудника туберкульозу, ступеня патогенності, сенсибілізованих властивостей та вмісту ліпідів, які залежать від рН середовища, протягом 180 щеплень культури 1–3 дні. Реверсія некислотостійких форм Mycobacterium bovis швидко зростаючого штаму до бактеріальних кислотостійких форм відбулася з наступних причин: утворення некислотостійких зерен у ниткоподібних M. bovis, трансформація та фрагментація некислотостійких ниткоподібних форм у кислотостійкі паличкоподібні бактерії та вихід із некислотостійких ниткоподібних кислотостійких форм M. bovis. Було встановлено, що збільшення кількості пасажів M. bovis швидко зростаючого штаму через середовище при рН 6,7 призводило до вірогідного зниження (p <0. 05) за вмістом загальних ліпідів; фракції фосфоліпідів, триацилгліцеринів та ефірів стерину; і збільшення кількості діацилгліцеринів, стеринів та вільних жирних кислот (FFA). Встановлено, що зменшення насичених та довголанцюгових жирних кислот та збільшення ненасичених та коротколанцюгових жирних кислот супроводжувалося втратою вірулентності мікобактерій. З 19 FFA дев'ять мали тенденцію зникати з клітинної стінки.
Хронологія морфологічних форм швидко зростаючого штаму Mycobacterium bovis
Ткаченко Олексій Андрійович http://orcid.org/0000-0003-0978-6575 Білан Марина Володимирівна https://orcid.org/0000-0003-3178-201X Глебенюк Володимир Володимирович https://orcid.org/0000-0001-5599-651X Алексєєва Наталія Вікторівна https://orcid.org/0000-0003-1984-5209
Keywords: virulence; вірулентність; Mycobacterium bovis; Mycobacterium bovis; nutrient medium; живильне середовище; passage; пасаж; strain; штам